Scalable and Isotropic Expansion of Tissues with Simply Tunable Expansion Ratio. Issue 22 (30th September 2019) - Park, Han‐Eol; Choi, Dongkil; Park, Ji Su; Sim, Changgon; Park, Sohyun; Kang, Sunah; Yim, Hyunsoo; Lee, Myungsun; Kim, Jaeyoun; Pac, Jinyoung; Rhee, Kunsoo; Lee, Junho; et al.
Abstract: Tissue expansion techniques physically expand swellable gel‐embedded biological specimens to overcome the resolution limit of light microscopy. As the benefits of expansion come at the expense of signal concentration, imaging volume and time, and mechanical integrity of the sample, the optimal expansion ratio may widely differ depending on the experiment. However, existing expansion methods offer only fixed expansion ratios that cannot be easily adjusted to balance the gain and loss associated with expansion. Here, a hydrogel conversion‐based expansion method is presented, that enables easy adjustment of the expansion ratio for individual needs, simply by changing the duration of a heating step. This method, termed ZOOM, isotropically expands samples up to eightfold in a single expansion process. ZOOM preserves biomolecules for post‐processing labelings and supports multi‐round expansion for the imaging of a single sample at multiple zoom factors. ZOOM can be flexibly and scalably applied to nanoscale imaging of diverse samples, ranging from cultured cells to thick tissues, as well as bacteria, exoskeletal Caenorhabditis elegans, and human brain samples. Abstract : ZOOM, a new tissue expansion technique based on the hydrogel conversion reaction, is developed to enable scalable and isotropic expansion of biological samples with easily tunable expansion ratio (up to eightfold). This method allows for simple and flexible expansion of a wide range of biological samples, from bacteria to human brain tissues, for super‐resolution imaging of samples with ordinary microscopes.